2000
DOI: 10.1093/jn/130.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Rye Bread Decreases Serum Total and LDL Cholesterol in Men with Moderately Elevated Serum Cholesterol

Abstract: The objective of this study was to determine the hypocholesterolemic effects of whole meal rye and white wheat breads in healthy humans with elevated serum cholesterol concentrations, and the changes in plasma glucose and insulin concentrations during rye and wheat bread periods. The subjects were 18 men and 22 women with baseline serum cholesterol concentration of 6.4+/-0.2 mmol/L. The study design was a 2x4-wk crossover trial during which each subject randomly consumed rye and wheat breads (20% of daily ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(65 citation statements)
references
References 31 publications
4
60
0
Order By: Relevance
“…In addition, high magnesium content and polyphenols in whole grains might also provide some other reasons (60,61). Results from randomized controlled trials have shown that increased consumption of whole grains can contribute to a decrease in blood pressure (62,63) and lipid profiles (64,65), and an increase in insulin sensitivity (66). Plasma concentrations of antioxidants, including vitamin E, selenium, and phenolic compounds, increase in parallel with increased consumption of whole grains (60), and this could reduce the risk of cancer and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high magnesium content and polyphenols in whole grains might also provide some other reasons (60,61). Results from randomized controlled trials have shown that increased consumption of whole grains can contribute to a decrease in blood pressure (62,63) and lipid profiles (64,65), and an increase in insulin sensitivity (66). Plasma concentrations of antioxidants, including vitamin E, selenium, and phenolic compounds, increase in parallel with increased consumption of whole grains (60), and this could reduce the risk of cancer and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Rye bread, compared to wheat bread, has some positive effects. One of themlowers the level of cholesterol in blood [50]. The cholesterol is seen as one of the prerequisites for cardiovascular diseases, that are responsible for more than a half of deaths in Lithuania [51].…”
Section: Changes In Growing Of Health-friendly Food Crops and Productmentioning
confidence: 99%
“…Health outcomes investigated in intervention studies in relation to rye consumption include: blood cholesterol levels (Lundin et al, 2004;Leinonen et al, 2000), cholesterol absorption (Hallikainen et al, 2006), improved insulin and glucose metabolism (Laaksonen et al, 2005;Lundin et al, 2004;Juntunen et al, 2003;McIntosh et al, 2003;Nygren et al, 1984), inhibition of prostate 37 38 cancer progression (Landberg et al, 2010;Bylund et al, 2003) and improved bowel function and easing of constipation (Holma et al, 2010;Gråsten et al, 2007;Hongisto et al, 2006;McIntosh et al, 2003;Gråsten et al, 2000). Regarding the development of type 2 diabetes, epidemiological reports indicate a protective association of whole-grain consumption (Priebe et al, 2008).…”
Section: Health Effectsmentioning
confidence: 99%